Study of phase reactances of special-purpose transformers during diagnostics of the excitation system of the electromagnetic scattering field - Zinovkin, Volodymyr; Tretiakov, Andrii (Національний технічний університет "Харківський політехнічний інститут", 2025)
The study of phase reactances of special-purpose transformers was conducted for the diagnostics of electromagnetic scattering excitation systems. Special attention is paid to assessing the technical condition of power transformers that supply energy-intensive technological complexes, as the current and voltage in them change according to complex periodic laws, leading to asymmetrical modes and accidents. To improve the reliability of transformer equipment, there is a need to develop specialized microprocessor and software tools for automated analysis and prevention of failures. Accident analysis has shown that electromagnetic scattering excitation systems are the most frequently damaged elements. A methodology for investigating the phase short-circuit resistances of power transformers with complex galvanic winding connections without disassembling the tank is proposed. The research aims to obtain reliable information about the current technical condition of transformer windings based on measured external parameters. The scientific novelty lies in establishing analytical dependencies between interphase short-circuit resistances and phase resistances. The developed program algorithm for automated analysis of winding conditions was implemented in “Turbo Pascal”. Experimental studies on a TRDN-63000/150/35 transformer confirmed the accuracy of the methodology and revealed deformation of the low voltage winding. Дослідження фазових реактивностей спеціалізованих трансформаторів було проведено для діагностики систем збудження електромагнітного розсіювання. Особлива увага приділяється оцінці технічного стану енергетичних трансформаторів, що живлять енергоємні технологічні комплекси, оскільки струм і напруга в них змінюються за складними періодичними законами, що призводить до асиметричних режимів та аварій. Для підвищення надійності трансформаторного обладнання виникла потреба у розробці спеціалізованих мікропроцесорних та програмних засобів для автоматизованого аналізу та запобігання відмовам. Аналіз аварійності показав, що найчастіше пошкоджуються системи збудження електромагнітного розсіювання. Запропоновано методику дослідження фазових опорів короткого замикання силових трансформаторів зі складними гальванічними з’єднаннями обмоток без розбирання бака. Мета дослідження – отримати достовірну інформацію про поточний технічний стан обмоток трансформатора на основі виміряних зовнішніх параметрів. Наукова новизна полягає у встановленні аналітичних залежностей між міжфазними опорами короткого замикання та фазовими опорами. Розроблений алгоритм програми для автоматизованого аналізу стану обмоток був реалізований на “Turbo Pascal”. Експериментальні дослідження на трансформаторі ТРДН-63000/150/35 підтвердили точність методики та виявили деформацію обмотки низької напруги.
Дослідження фазових реактивних опорів трансформаторів спеціального призначення в процесі діагностики системи збудження електромагнітного поля розсіювання
Keywords: power transformer; phase reactance; diagnostics; electromagnetic scattering; automated analysis; winding damage; силовий трансформатор; фазова реактивність; діагностика; електромагнітне розсіювання; автоматизований аналіз; пошкодження обмоток